Identification of Potential Bacteria on Several Lakes in East Java, Indonesia Based on 16S rRNA Sequence Analysis - Achmad Rodiansyah; Ainul Fitria Mahmudah; Mastika Marisahani Ulfah; Uun Rohmawati; Dwi Listyorini; Eko Agus Suyono; Sitoresmi Prabaningtyas (Bogor Agricultural University, Indonesia, 2021)
Four bacterial isolates from Ranu Pani and Ranu Grati in east java had been revealed to be potentials to produce IAA (PIS isolate), phosphate solubilizer (GPS isolate), cellulose hydrolysis (PSS isolate) and, amylum hydrolysis (PAS), two dominant bacterial isolates from Rani Pani (PØD isolate) and Ranu Grati (GØD isolate) which were co-cultured with microalgae promoted microalgae growth, yet its taxonomical position has not been clearly known. The aim of this study was to identify those bacterial isolates using 16S rRNA barcode. This research conducted by gDNA isolation, the 16S rRNA sequence was amplified using 27F and 1492R primers. Reconstructed phylogenetic trees and genetic distance analysis showed that the isolate PIS and PSS identified as Bacillus cereus Group closely related to Bacillus paramycoides. PAS isolate identified as Bacillus subtilis Group closely related to Bacillus amyloliquefaciens, GPS isolate identified as novel species in genus Enterobacter, and two dominant isolates (PØD and GØD) identified as Enterobacter cloacae complex closely related to Enterobacter cloacae. The genomic approach and additional phenotypes-examination are required to clarify its taxonomical position.